Pelatiahan Wirausaha kepada Kelompok Ibu-Ibu PKK pada UMKM Tahu Kelurahan Lewirato Kec. Mpuda Kota Bima - Puji Rahayu; Ita Purnama; Sandrawati Sandrawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This entrepreneurship training aims to enhance the skills and knowledge of PKK women’s groups in managing micro, small, and medium enterprises (MSMEs) focused on tofu production in Lewirato Subdistrict, Mpunda District, Bima City. The program is designed to equip participants with essential entrepreneurial insights and skills, particularly in improving the quality and quantity of tofu production, marketing strategies, and effective and sustainable business management. The training methods include lectures to deliver foundational material, group discussions to share experiences and solve problems collaboratively, and hands-on practice in the production and packaging process of tofu. It also covers the importance of product branding and the use of social media as a digital promotion tool to reach a wider market. Through this program, participants are expected to apply the knowledge gained to develop their businesses independently and professionally. With increased skills and confidence among PKK women in managing tofu MSMEs, it is also hoped that family income will rise and contribute positively to the local economy. This training represents a vital initial step toward achieving community economic independence through entrepreneurship.